Determinants of long-term quality of life in patients with differentiated thyroid carcinoma – a population-based cohort study in Sweden. (3rd March 2016) - Hedman, Christel; Djärv, Therese; Strang, Peter; Lundgren, Catharina Ihre
Abstract: Background : Although differentiated thyroid cancer (DTC) has an excellent prognosis and a low incidence of recurrence, lifelong follow-up and medication might be needed. The aim of this study was to clarify how living with a cancer diagnosis for many years affects health-related quality of life (HRQoL) in DTC patients in Sweden. Material and methods : From the national all-encompassing population-based Swedish Cancer Registry, 353 patients diagnosed with DTC between 1995 and 1998 were identified and invited to answer the HRQoL questionnaire SF-36 and a study-specific questionnaire, 14–17 years after their diagnosis. Data were compared with a reference population as well between subgroups of patients. Results : Of the patients with DTC, 279 (79%) answered the questionnaires. In all, only 19 (7%) reported a recurrence, however, as many as 134 (48%) stated that they still had concerns about having a recurrence. The HRQoL in those with a recurrence was significantly lower than those without concerns of a recurrence in five of eight domains (p < 0.001–0.049). Similarly, patients with concerns of a recurrence reported poorer HRQoL than those without concerns, with significantly lower values in five domains (p < 0.001–0.008). Those few who stated that their disease had given them a negative view on life reported poor HRQoL in all eight domains (p < 0.001–0.030). Conclusions : Even if DTC comes with an excellent prognosis, almost half of the patients, fully 15 years after diagnosis, worried about a recurrence which negatively impacted their HRQoL. Awareness among healthcare practitioners might improve information, supportive care and, in the end, the patient's HRQoL.